Decolorization of remazol brilliant blue R with laccase from Lentinus crinitus grown in agro-industrial by-products - ALMEIDA,PATRÍCIA H. (2018)
ABSTRACT Lentinus crinitus is a white-rot fungus that produces laccase, an enzyme used for dye decolorization. Enzyme production depends on cultivation conditions, mainly agro-industrial by-products. We aimed to produce laccase from Lentinus crinitus with agro-industrial by-products for dye decolorization. Culture medium had coffee husk (CH) or citric pulp pellet (CP) and different nitrogen sources (urea, yeast extract, ammonium sulfate and sodium nitrate) at concentrations of 0, 0.7, 1.4, 2.8, 5.6 and 11.2 g/L. Enzymatic extract was used in the decolorization of remazol brilliant blue R. CH medium promoted greater laccase production than CP in all evaluated conditions. Urea provided the greatest laccase production for CH (37280 U/L) as well as for CP (34107 U/L). In CH medium, laccase activity was suppressed when carbon-to-nitrogen ratio changed from 4.5 to 1.56, but the other nitrogen concentrations did not affect laccase activity. For CP medium, reduction in carbon-to-nitrogen ratio from 6 to 1.76 increased laccase activity in 17%. The peak of laccase activity in CH medium occurred on the 11th day (41246 U/L) and in CP medium on the 12th day (32660 U/L). The maximum decolorization within 24 h was observed with CP enzymatic extract (74%) and with CH extract (76%).